Determinación del perfil renal urea, creatinima , acido urico y glucosa en los afiliados del seguro social campesino del dispensario Voluntad de Dios, que asisten a la Unidad de Atención Ambulatoria R-9 de Santa Rosa , 2014. - Macas Duchicela, Jessica Anabel (2015)
The present investigation was to determiner Objective Titles Profile of renal urea, creatine , uric acid and glucose Affiliates Rural Social Security Dispensary God's will that aisten Unit Ambulatory Care Santa Rosa , for determination took blood samples Patient fasting , the What Were obtained and processed in the Clinical Laboratory of the Medical Unit using the spectrophotometer Humalyzer 2000 and reagents Working some 161 Patients total bathroom, once obtained values immunity tests Tabulados and correlated with the variables of age , gender and Reference .